2022
DOI: 10.1111/poms.13577
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App Adoption and Its Differential Impact on Consumer Shopping Behavior

Abstract: The mobile application (app) market is one of the fastest growing markets in recent years. In this study, we investigate how app adoption changes customers’ hotel booking behaviors using a dataset of around 16,000 randomly selected customers’ hotel booking and stay information from one of the largest hotel chains in China. Our analyses find that customer purchase frequency and total sales increased after app adoption. Additional investigation shows that customers’ search behaviors also evolved post‐adoption. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In recent OM literature, there has been a growing trend of reporting comparisons for both the means of the covariates and the distribution of the propensity scores, following the second and third evaluation strategies discussed above (e.g., Adbi et al, 2022; Ba et al, 2022; Pu, 2022). While there is no golden standard for evaluating matching quality, we strongly recommend researchers to adopt a proactive and transparent approach by reporting both summary statistics and empirical distributions of the matched samples.…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…In recent OM literature, there has been a growing trend of reporting comparisons for both the means of the covariates and the distribution of the propensity scores, following the second and third evaluation strategies discussed above (e.g., Adbi et al, 2022; Ba et al, 2022; Pu, 2022). While there is no golden standard for evaluating matching quality, we strongly recommend researchers to adopt a proactive and transparent approach by reporting both summary statistics and empirical distributions of the matched samples.…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…Social media has also shown potential to improve operations, for example, ramping up inventory or allocating more storage for items trending on social media, assessing the importance of on‐time delivery, and extracting reasons for product returns from social media responses, extracting consumer sentiment to get advanced demand forecasts or new product assortments (Rooderkerk et al., 2022), and optimizing resources and relief packages during COVID (Gour et al., 2022). Research has also shown that revealing preferences and adopting a platform could reduce price sensitivity and increase purchasing behavior (Ba et al., 2022). Furthermore, advancements in technology can disrupt the existing production management processes through the use of new algorithms and optimization models with intelligent operations decisions (Choi et al., 2022).…”
Section: Literaturementioning
confidence: 99%
“…Ba et al. (2021) use PSM with observables such as gender, third‐party account association, availability of private information, nationality, membership level, and the amount of money users spend. Ba et al.…”
Section: Identification Strategies For Assessing Causality In Pom Emp...mentioning
confidence: 99%
“…Ba et al. (2021) also compare the distribution of the covariates before and after matching, including t ‐tests and Kolmogorov–Smirnov tests 12 . Mejia et al.…”
Section: Identification Strategies For Assessing Causality In Pom Emp...mentioning
confidence: 99%
See 1 more Smart Citation